The Opinion of Visitors on the Touristic Attractions and Services of the Esterhazy Castle of Fertőd - Bodrogai, László A.; Szigeti, Orsolya (Applied Studies in Agribusiness and Commerce, 2018)
The lately renovated Esterhazy Palace is one of Europe’s biggest Baroque palaces. This paper examines the visitors’ opinion of this worldwide famous palace. This survey-based study was carried out in 2016/2017. The sample was of 800 people, using paper-based questionnaire. It emerged from the study that the visitors needed to be separated analyzed differently under and above 18 years of age, because the push and pull factors vary significantly. Other words, the adult visitors (persons, families) decided themselves to go and see or not, but the young people were influenced by their teachers. Other important lessons of the study was that the visiting process does not end with the viewing of rooms and tools, but the different souvenirs and providing further information, and services are also part of it. This is evidenced by the fact that the worst rating was given by the related service. Organizing and ensuring this is an important task of the management of the palace. JEL Classification: M3. O18, Z32